Indigenous knowledge systems for the management of the Barotse Flood Plain in Zambia and their implications for policy and practice in the developing world - Mapedza, Everisto D.; Rashirayi, T.; Xueliang, C.; Haile, Alemseged Tamiru; van Koppen, Barbara; Ndiyoi, M.; Senaratna Sellamuttu, Sonali (Elsevier, 2022)
Most development planners and practitioners have often wrongly assumed that solutions for community challenges lie within the “western scientific knowledge” only. However, the recent studies have highlighted the relevance of Indigenous Knowledge to inform western scientific solutions. This study is on the Barotse Flood Plain of the Western Province of Zambia. Flood inundation understanding by the local communities has direct implications for their livelihood options and for the well-being of their households. The research found that there are a number of important local knowledge systems that are early warning systems based on observations of weather, water level and landscape, and animal behavior, which are widely disseminated through a specific communication network. The chapter concludes with a discussion on how the integration of Western scientific and Indigenous Knowledge Systems will better inform interventions to improve livelihood options for the communities within the Barotse Flood Plain and policy and practice within the developing world at large.